Introduction to the Special Section on “Translational Models of Prefrontal Cortical Function”. - Baxter, Mark G. (Behavioral Neuroscience, 2011)
Impaired functioning of the prefrontal cortex is particularly prominent in many forms of psychopathology and in degenerative brain diseases. Because it is challenging to draw causal links between specific brain abnormalities and impaired cognition in these conditions, research using nonhuman animals has a key role to play in elucidating the neurobiological mechanisms of prefrontal cortex function and aiding the search for treatments. This role is clearly illustrated in the review articles and original research reports in this special section. Taken together, these papers demonstrate the insights that have already been gained from research with nonhuman animals as well as the work that still needs to be done to attain the goal of understanding human prefrontal cortical function in both health and disease. Reprinted by permission of the publisher.